A host of hypercholesterolaemic homozygotes in South Africa. Issue 6241 (6th September 1980) - Seftel, H C; Baker, S G; Sandler, M P; Forman, M B; Joffe, B I; Mendelsohn, D; Jenkins, T; Mieny, C J
Abstract : From 1972 to 1979 34 patients with homozygous familial hypercholesterolaemia were seen in one clinic in Johannesburg. All were Afrikaners and most lived in Transvaal Province. Their epidemiological, genetic, clinical, and biochemical characteristics were studied. The course of the disease varied considerably among the 34 patients, with no fewer than six surviving into their fourth or fifth decades. In some patients arterial atheroma was severe while cutaneotendinous xanthomas were slight and vice versa. Coronary heart disease was common but peripheral and cerebral arterial disease was rare. Another prominent finding was high concentrations of low-density lipoprotein cholesterol coupled with low high-density lipoprotein cholesterol values. The prevalences of homozygotes and heterozygotes with familial hypercholesterolaemia in Transvaal Afrikaners, calculated from this group of patients, were 1 in 30, 000 and 1 in 100 respectively. These figures are the highest ever reported and may help to explain why South African whites have the highest death rate from coronary heart disease in the Western world.